Perjanjian Jual Beli Tanah Hak Milik Debitur Pailit yang Dijaminkan di Bank - Leomardo Ebedkena Tabuni; I Made Arjaya; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2020)
In connection with the sale and purchase agreement for the land owned by a bankrupt debtor who is guaranteed at the bank, of course, there will be a consequence of a legal action. The result of the legal action in question is regarding the transfer of land title if the debtor breaks his promise or does not carry out his obligations. Creditors holding Guarantee Rights Guarantee (separatist creditors) may execute the guarantee, as if there was no bankruptcy. However, in exercising his executive rights, there is a time limit for separatist creditors in accordance with Article 56 of the Bankruptcy Law. After passing this period of time, the curator then carries out the management and settlement under the supervision of the supervisory judge. The purpose of this research is to study and find out about the legal arrangement and procedures for the settlement of sale and purchase of land owned by a bankrupt debtor which are guaranteed at the bank. This study uses a normative legal research method, with a statutory approach and a conceptual approach. The results of this study are: firstly, the credit agreement creates a debt and credit relationship, in which the debtor is obliged to pay back the loan given by the creditor (bank); secondly, in accordance with the requirements for a debtor who has two or more creditors and there is a debt and one debt is due and can be collected. After fulfilling these requirements, those who have been registered through the clerk of the court, further examination by the Chief Justice will be carried out to obtain a permanent bankruptcy decision for Ninety days, and ultimately, a summon of the parties to a verification meeting is carried out.